Effect of ethifone cocentrations, size and seeds viability in some physiological features and viable material in local pea ( Pisum sativum L.) - Mohammed Abdulelah Mohammed (College of Education for Pure Sciences, 2009)
ABSTRACT The study was carried out in a field of khorsebat region (north-east of Mosul city) during season 2001-2002 with silty loam soil in order to investigate the effect of different Ethephon concentrations (0, 240, 480, 720) gr/ha a.i. on local species of pea (Pisum sativum L.). the plants were germinated from large and small seeds as well as low and high viability. In order to decreased the viability, the seeds were exposured to 100% humidity and 40 Co for 48 hours. The seeds were grown under rain-fed irrigation. The result showed a significant decrease in plant length, Leaf Area Duration (L.A.D.), Relative Growth Rate (R.G.R.), Biomas Duration (B.M.D.) and Net Assimilation Rate (N.A.R.) when increasing the concentration of Ethephon more than 480 gr./ha. But on the other hand, the plants decreased at the minimum rates of Ethephon 240 gr./ha. Moreover, a significant increase was observed for large seeds as compared with the small seeds in all the studied descriptions even in low viability. Furthermore, the minimum concentration of Ethephon increased the studied descriptions or the low viability seeds previously mentioned.